Taxonomic revision of the spider genus Ixchela Huber, 2000 (Araneae: Pholcidae), with description of ten new species from Mexico and Central America - Valdez-Mondragón, Alejandro (Zootaxa, 2013)
A taxonomic revision of the genus Ixchela Huber, 2000 is presented. The previously described five species are redescribed with new taxonomic information and new distribution records. The males of Ixchela placida (Gertsch, 1971) and Ixchela simoni (O. Pickard-Cambridge, 1898) are described for the first time. Ten new species are described, nine from Mexico and one from Honduras: Ixchela mixe new species, Ixchela huberi new species, Ixchela juarezi new species, Ixchela grix new species, Ixchela taxco new species, Ixchela franckei new species, Ixchela tzotzil new species, Ixchela santibanezi new species, Ixchela huasteca new species, and Ixchela viquezi new species. Identification keys for males and females are presented.